2020
DOI: 10.1097/pec.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of 3% Hypertonic Saline Hyperosmolar Therapy on Intubated Children With Isolated Traumatic Brain Injury by Cerebral Oximetry in a Pediatric Emergency Setting

Abstract: Background: Intubated pediatric patients with isolated traumatic brain injury (TBI) are a diagnostic challenge for early detection of altered cerebral physiology instigated by trauma-induced increased intracranial pressure (ICP) while preventing secondary neuronal damage (secondary insult detection) and assessing the effects of increased ICP therapeutic interventions (3% hypertonic saline [HTS]). Invasive brain tissue oxygen monitoring is guiding new intensive care unit TBI management but is not pediatric emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(737 reference statements)
0
1
0
Order By: Relevance
“…A retrospective study 24 compared 3%, 6%, and 12% HTS in 43 children with sTBI and, surprisingly, found a concentration-dependent reduction in ICP of 4.5, 6.6, and 10.5 mm Hg, respectively, despite using equimolar doses of the medications. Three studies [25][26][27] addressed prehospital or emergency department use. Finally, 2 systematic reviews 28,29 concluded that there was a paucity of high-quality data, making it difficult to draw conclusions.…”
Section: Current Recommendations For Hyperosmolar Therapymentioning
confidence: 99%
“…A retrospective study 24 compared 3%, 6%, and 12% HTS in 43 children with sTBI and, surprisingly, found a concentration-dependent reduction in ICP of 4.5, 6.6, and 10.5 mm Hg, respectively, despite using equimolar doses of the medications. Three studies [25][26][27] addressed prehospital or emergency department use. Finally, 2 systematic reviews 28,29 concluded that there was a paucity of high-quality data, making it difficult to draw conclusions.…”
Section: Current Recommendations For Hyperosmolar Therapymentioning
confidence: 99%